The influence of socio-formative teaching on the academic performance of students at a public university - Valderrama Puscan, Marlon Walter; Rondo Cuba, Gabriel; Soplapuco Chira, Jonathal Jesus (LACCEI, 2025)
The general objective of the research was to determine the influence of socio-formative teaching on the academic performance of students at a public university. This study adopted a quantitative approach, basic type, with a non-experimental, cross-sectional design and causal correlational level. The population was made up of 100 chemical engineering students, selected through census sampling. Two validated and reliable questionnaires were used: one to evaluate socio-formative teaching and another specifically designed to measure academic performance from a comprehensive approach. The results showed a moderate positive correlation (Rho = 0.430, p = 0.000) between socio-formative teaching and academic performance, it was also obtained R2= 0,15 explaining 15% of its variability, with teacher support as the most influential dimension (Rho = 0.484, p = 0.000). It is concluded that socio-formative teaching significantly improves academic performance by promoting comprehensive skills, motivation and commitment, aligning with previous studies that highlight the importance of this pedagogical approach in diverse educational contexts.